Chemical admixtures in cement mortar: long-term performance evaluation against biogenic acid attack - Umar, Mohd; Haque, M.D. Najeebul; Mohammed, M.S. Haji Sheik (Journal of Structural Engineering, 2024)
When biogenic acid reacts with cement hydrates, physical and chemical changes occur in the cement mortar, whichcan cause premature deterioration of exposed concrete structures. The present study evaluates the performance ofchemical admixtures, viz., styrene acrylic ester based polymer (SAP) and sodium nitrite based corrosion inhibitingadmixture (SNI) in cement mortar exposed to two strong inorganic acids, hydrochloric acid (HCl) and sulphuric acid(H2SO4). Its aim is to investigate the potential chemical changes in exposed cement mortar to properly understand thedegradation mechanism by these acids. Post-exposure evaluation investigates the changes in the strength, variations inlength/mass of the specimens, and variations in the pH of the leachant (exposed medium). Fourier transform infraredspectroscopy (IR) was performed to analyse the associated chemical changes in the cement mortar due to acid exposure.Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) were used to study microstructuraltransformations and final phase products associated with the chemical changes. Findings from the study reveal higherdegradation caused by H2SO4 medium than HCl medium, irrespective of SAP/SNI incorporation, due to a significantdifference in their mechanisms of attack, which was linked to their calcium salt solubility along with its adheringaffinity to the cement matrix. Due to its instability in acidic media, SAP incorporation into cement mortar results ininferior performance compared to control mortar. The overall performance of SNI addition in cement mortar wasfound to be significantly superior to control mortar in post-exposure evaluation. Results from IR analysis along withSEM-EDS characterization confirm the least deterioration and improved microstructural properties of cement mortaradmixed with SNI.